2022
DOI: 10.1039/d2ee02199d
|View full text |Cite
|
Sign up to set email alerts
|

An interactive design for sustainable oxygen capacity in alkali-ion batteries

Abstract: Nonhysteretic and reversible (nHR) oxygen redox is desirable for high-energy-density cathodes in lithium-ion batteries (LIBs); however, serious challenges remain. An interactive design concept that mimics the nHR anionic activity of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Toward this goal, oxygen anionic redox (OAR) in Li-and Na-ion oxide cathodes has been the topic of sustained interest owing to its ability to furnish extra high-voltage capacity beyond that of the orthodox transition metal (TM) redox. [1][2][3][4] Unfortunately, such extra capacity comes with a price since the OAR-active cathodes typically suffer from sluggish kinetics, huge voltage hysteresis, and persistent voltage fading over cycling. 5,6 In addition, the OAR has been revealed to implicate a series of oxygen-centred structural rearrangements that are thermodynamically favorable, during which its reversibility or cyclability is progressively compromised with prolonged cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this goal, oxygen anionic redox (OAR) in Li-and Na-ion oxide cathodes has been the topic of sustained interest owing to its ability to furnish extra high-voltage capacity beyond that of the orthodox transition metal (TM) redox. [1][2][3][4] Unfortunately, such extra capacity comes with a price since the OAR-active cathodes typically suffer from sluggish kinetics, huge voltage hysteresis, and persistent voltage fading over cycling. 5,6 In addition, the OAR has been revealed to implicate a series of oxygen-centred structural rearrangements that are thermodynamically favorable, during which its reversibility or cyclability is progressively compromised with prolonged cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Phase transition occurs in conjunction with the dynamic variation of the Li concentration throughout the charging and discharging operations. [44][45][46] The three model systems were prepared by chemical alloying, fabrication of a composite, and subsequent in-cell electrochemical reactions. A brief illustration of the chemical reaction is shown in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The motivation in utilizing the OR for Nabased layered oxides was systematically derived from a well-known Li-excess Mn oxide (Li 2 MnO 3 ) that exhibits the anionic oxidation upon charging for lithium-ion batteries (LIBs), leading to the design of O3-type Na[Li 1/3 Mn 2/3 ]O 2 , operated by the pure oxygen oxidation above ≈4.0 V versus Na + /Na, delivering a high theoretical capacity of 285 mAh g −1 (if all Na ions are used) during desodiation. [9][10][11][12][13][14] This mechanism-driven computational design resulted in the successful synthesis of a Na intercalation cathode, and advanced experimental analyses clearly confirmed that the anionic reaction compensated for the charge imbalance induced by Na extraction from the host material. [15][16][17] Unfortunately, this promising cathode produces undesired electrochemical features, such as a large irreversible capacity and severe voltage drop in the subsequent discharge process after the first activation.…”
Section: Introductionmentioning
confidence: 91%